Mucosal immunity against influenza induced by attenuated recombinant Sendai virus. (October 2011) - Imamura, Tadatsugu; Oshitani, Hitoshi
Evaluation of: Le TV, Mironova E, Garcin D, Compans RW. Induction of influenza-specific mucosal immunity by an attenuated recombinant Sendai virus. PLoS One 6(4), e18780 (2011). Live-attenuated influenza vaccines (LAIVs) have been shown to be more immunogenic and capable of inducing a broader immune response than inactivated vaccine. However, use of LAIVs is still limited owing to the safety concerns. Le et al. generated an attenuated recombinant Sendai virus – GP42-H1 expressing the hemagglutinin (HA) gene of influenza A virus. The HA protein was expressed on the cell surface of CV-1 cells infected with GP42-H1. Intranasal immunization of mice with GP42-H1 induced HA-specific IgG and IgA antibodies in sera and mucosal sites without causing any disease symptoms. Immunized mice were also protected from lethal dose challenge of influenza A virus.